2014
DOI: 10.2478/raon-2013-0035
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and malignancy risk of focal colorectal incidental uptake detected by 18F-FDG-PET or PET/CT: a meta-analysis

Abstract: BackgroundThe aim of the study was to meta-analyze published data about prevalence and malignancy risk of focal colorectal incidentalomas (FCIs) detected by Fluorine-18-Fluorodeoxyglucose positron emission tomography or positron emission tomography/computed tomography (18F-FDG-PET or PET/CT).MethodsA comprehensive computer literature search of studies published through July 31st 2012 regarding FCIs detected by 18F-FDG-PET or PET/CT was performed. Pooled prevalence of patients with FCIs and risk of malignant or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 30 publications
4
46
0
1
Order By: Relevance
“…However, a high SUVmax may also be found in various benign conditions because 18 FDG is not a neoplasm-specific substance. Indeed, Treglia et al ( 20 ) showed that the SUVmax alone should not be used to differentiate between a malignant, premalignant and benign incidental colonic focal uptake because a significant overlap of the SUVmax was found between these groups. Our results are similar to those of their report in this point, although our data clearly demonstrate that advanced neoplasms had a significantly higher mean SUVmax, compared with that in non-advanced lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, a high SUVmax may also be found in various benign conditions because 18 FDG is not a neoplasm-specific substance. Indeed, Treglia et al ( 20 ) showed that the SUVmax alone should not be used to differentiate between a malignant, premalignant and benign incidental colonic focal uptake because a significant overlap of the SUVmax was found between these groups. Our results are similar to those of their report in this point, although our data clearly demonstrate that advanced neoplasms had a significantly higher mean SUVmax, compared with that in non-advanced lesions.…”
Section: Discussionmentioning
confidence: 99%
“…With its increasing availability and use in cancer patients, it is not uncommon to detect incidental 18 F‐FDG uptake on PET/CT in sites other than where the primary cancer is known or suspected, posing a diagnostic challenge to clinicians. A common site is the large bowel, where the prevalence of incidental focal colorectal 18 F‐FDG uptake detected by PET or PET/CT is estimated at 3.6% . While diffuse and segmental patterns of 18 F‐FDG uptake are attributed to benign or inflammatory causes, focal uptake is associated with a significant risk of neoplasia .…”
Section: Introductionmentioning
confidence: 99%
“…A common site is the large bowel, where the prevalence of incidental focal colorectal 18 F-FDG uptake detected by PET or PET/CT is estimated at 3.6%. 3 While diffuse and segmental patterns of 18 F-FDG uptake are attributed to benign or inflammatory causes, focal uptake is associated with a significant risk of neoplasia. [4][5][6][7][8][9][10][11] Given that colorectal cancer may be insidious in onset and run a silent course until late, these radiological findings should not be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…En particulier, les méthodes de reconstruction sont identiques permettant d'homogénéiser les images et les valeurs de SUVmax. Dans la méta-analyse de Treglia et al de 2014 [28], ils n'ont pas pu définir de valeur de SUVmax en fonction de la nature histologique des lésions à cause de la disparité des caméras TEP/TDM. Un projet d'uniformité des paramètres d'injection, d'acquisition et de reconstruction devrait voir le jour dans les années qui viennent mais, en attendant, de grosses disparités existent sur le territoire français.…”
Section: Les Limites De Notre éTudeunclassified